Nutritional recommendations for divers - Benardot, D.; Zimmermann, W.; Cox, G. R.; Marks, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Competitive diving involves grace, power, balance, and flexibility, which all require satisfying daily energy and nutrient needs. Divers are short, well-muscled, and lean, giving them a distinct biomechanical advantage. Although little diving-specific nutrition research on performance and health outcomes exists, there is concern that divers are excessively focused on body weight and composition, which may result in reduced dietary intake to achieve desired physique goals. This will result in low energy availability, which may have a negative impact on their power-to-weight ratio and health risks. Evidence is increasing that restrictive dietary practices leading to low energy availability also result in micronutrient deficiencies, premature fatigue, frequent injuries, and poor athletic performance. On the basis of daily training demands, estimated energy requirements for male and female divers are 3,500 kcal and 2,650 kcal, respectively. Divers should consume a diet that provides 3-8 g/kg/day of carbohydrate, with the higher values accommodating growth and development. Total daily protein intake (1.2-1.7 g/kg) should be spread evenly throughout the day in 20 to 30 g amounts and timed appropriately after training sessions. Divers should consume nutrient-dense foods and fluids and, with medi- cal supervision, certain dietary supplements (i.e., calcium and iron) may be advisable. Although sweat loss during indoor training is relatively low, divers should follow appropriate fluid-intake strategies to accommodate anticipated sweat losses in hot and humid outdoor settings. A multidisciplinary sports medicine team should be integral to the daily training environment, and suitable foods and fluids should be made available during prolonged practices and competitions.